An Analysis of Role-play Simulated Content Creation and Its Impact on EFL Students Speaking Skills - Saputra, Ramadhani; Yuliati (PROJECT (Professional Journal of English Education), 2026)
This study aims to clarify how simulation and role-play can improve the speaking skills of English as a Foreign Language (EFL) learners, examining their effectiveness in increasing fluency, comprehension, and interaction, while also building students' confidence and motivation to use English. Within this framework, Task-Based Language Teaching (TBLT) plays a crucial role in the research, emphasizing the significance of using meaningful tasks as the core component of the language learning process. A key development in this study is the combination of content creation with social media to support language learning. In today's digital era, the ability to create content has become a vital skill, and its integration into EFL teaching can greatly enhance student involvement. The research employs a thematic analysis approach, examining the learning experiences of students and providing detailed insights for future research efforts. The main research question focuses on how this teaching method can improve students' abilities. The findings provide valuable information for teachers about integrating modern technology into language teaching. Ultimately, this study seeks to understand how students interact with social media and content creation, while offering insights into the potential of these contemporary tools in creating an engaging and dynamic atmosphere for language learning.